Damage identification of a target substructure with moving load excitation - Li, J.; Law, S.S. (Mechanical systems and signal processing, 2012)
This paper presents a substructural damage identification approach under moving vehicular loads based on a dynamic response reconstruction technique. The relationship between two sets of time response vectors from the substructure subject to moving loads is formulated with the transmissibility matrix based on impulse response function in the wavelet domain. Only the finite element model of the intact target substructure and the measured dynamic acceleration responses from the target substructure in the damaged state are required. The time-histories of moving loads and interface forces on the substructure are not required in the proposed algorithm. The dynamic response sensitivity-based method is adopted for the substructural damage identification with the local damage modeled as a reduction in the elemental stiffness factor. The adaptive Tikhonov regularization technique is employed to have an improved identification result when noise effect is included in the measurements. Numerical studies on a three-dimensional box-section girder bridge deck subject to a single moving force or a two-axle three-dimensional moving vehicle are conducted to investigate the performance of the proposed substructural damage identification approach. The simulated local damage can be identified with 5% noise in the measured data. ► Substructural approach of damage identification without information of whole structure. ► New numerical technique based on response reconstruction approach. ► No need to calculate or measure the interface forces. ► For application with the background of vehicles moving on top of bridge deck.